The Effect of Rare Earth Metal Doping in Bi2/3Cu3Ti4O12 Ceramic on Microstructure, Dielectric and Electrical Properties - Prajapati D.; Rai V.S.; Kumar V.; Verma M.K.; Kumar A.; Singh N.B.; Mandal K.D. (My University, 2025)
An Aurivillius oxide, Bi(2/3)-xGdxCu3Ti4O12 (x = 0.05, 0.10, and 0.20) ceramic designated as BGCTO-0.05, BGCTO-0.1 and BGCTO-0.2 has been fabricated by modified solid-state route resemble with semi wet route and characterized by using various techniques including XRD, SEM, EDX, TEM and XPS for getting information about phase formation, morphology, particle size distribution and oxidation state of elements of synthesized ceramics. X-ray diffraction pattern confirmed the single-phase formation of BGCTO ceramic. The crystalline nature of BGCTO ceramic for few selected compositions, x = 0.05, 0.10, and 0.20 were observed by TEM analysis. Further, particle size was determined with the help of Image J software and found to be 90.85 ± 5 nm, 75.35 ± 5 nm and 72.43 ± 5 nm, respectively for BGCTO-0.05, BGCTO-0.1 and BGCTO-0.2 ceramic. The dielectric permittivity (εr) as well as tangent loss (tan δ) was observed at room temperature and 1 kHz for all synthesized ceramics. The electrical behaviour of BGCTO ceramic revealed the presence of semiconducting grain separated by grain boundaries. © 2023, The Korean Institute of Electrical and Electronic Material Engineers.